Diseño de una ruta turística para promocionar los atractivos turísticos del cantón Quevedo, año 2021 - Mero Muñoz, Tatiana Cecibel (2021)
The present research work consists of designing a tourist route to promote the tourist attractions of the Canton Quevedo year 2021, located in the province of Los Ríos, whose main objective is to promote our city with quality and that it diversifies through the resources or natural tourist attractions that we have. The research was developed with an analytical and descriptive character. This research work began with the development of the theoretical foundation, for which a search of the variables was carried out in the different available sources, to achieve the correct definition and from there begin with the development of the case. In chapter one points out the proposal of a tourist route design that allows promoting the tourist attractions of Canton, which will contribute to solving the problems, through applicable strategies, reaching the interest of national and local tourists. Chapter two contains the detected situations where the tourist places of the city and the attractions of each one are detailed, in the proposed solutions a guide with clear information for tourists was presented, as well as the conclusions and recommendations pertinent to the investigation. The purpose of this project is that the tourist promotion is a contribution to the tourism of the Quevedo Canton, because by promoting the sites that the Canton has in an appropriate way, with a well-directed promotion through different means such as posters, volantes, or social networks, among others, focused on achieving the increase in the influx of visitors being the population the main beneficiary through the economic resources that are get from the tourist activity.